A new species of Rostrozetes (Acari: Oribatida: Haplozetidae) from Brazil - Bomfim, Grecilane S.; Delabie, Jacques H.c.; Oliveira, Anibal R. (Zootaxa, 2024)
The mite Rostrozetes achilles sp. nov. is described from adult specimens collected from nests of the ant Camponotus cingulatus (Formicidae) in dry cacao pods and the surrounding soil–litter interface in a cacao plantation of Ilhéus, state of Bahia, northeastern Brazil. This is the sixth Rostrozetes species known to have heteromorphic notogastral setae. The species name refers to the apparent use of its laminar discidium to protect its ‘heel’, the joint between tarsus and pretarsus, during leg IV flexion. Other possible functions for it are also discussed.